2007
DOI: 10.1111/j.1462-5822.2006.00843.x
|View full text |Cite
|
Sign up to set email alerts
|

The Helicobacter pylori virulence factor CagA promotes Erk1/2-mediated Bad phosphorylation in lymphocytes: a mechanism of CagA-inhibited lymphocyte apoptosis

Abstract: SummaryThe Helicobacter pylori virulence factor, CagA, is causally linked to lymphoma of gastric mucosaassociated lymphoid tissue (MALT). However, it is unclear how CagA promotes the development of gastric MALT lymphoma. We investigated whether CagA modulates the activation of Erk1/2 and their downstream apoptosis regulators in B lymphocytes. Transfection of B1 lymphocytes with cagA transiently increased Erk1/2 phosphorylation, which was negatively regulated by MKP-1 and MKP-6. Activation of Erk1/2 led to phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 49 publications
1
32
0
Order By: Relevance
“…52 Two in vitro studies have also shown that B-lymphocyte apoptosis can be inhibited in the presence of intracellular CagA through the decreased transcription and the accumulation of p53 or the ERK1/2-mediated phosphorylation at Ser 112 of BAD. 53,54 Although our findings and those of others suggest that CagA can affect lymphomagenesis directly through the regulation of CagArelated signal transduction in gastric MALT lymphoma, other H pylori-related pathways associated with lymphoid neoplasms may also be involved. Our preliminary results showed that polymorphism of IL-22 plays an important role in the development of MALT lymphoma and that IL-22 expression is associated with H pylori dependence in gastric MALT lymphoma (F. Liao, Y. C. Hsu, S.H.K., et al, unpublished data, May 15, 2013).…”
Section: Direct Effects Of H Pylori On B-cell Proliferation In Gastrimentioning
confidence: 55%
“…52 Two in vitro studies have also shown that B-lymphocyte apoptosis can be inhibited in the presence of intracellular CagA through the decreased transcription and the accumulation of p53 or the ERK1/2-mediated phosphorylation at Ser 112 of BAD. 53,54 Although our findings and those of others suggest that CagA can affect lymphomagenesis directly through the regulation of CagArelated signal transduction in gastric MALT lymphoma, other H pylori-related pathways associated with lymphoid neoplasms may also be involved. Our preliminary results showed that polymorphism of IL-22 plays an important role in the development of MALT lymphoma and that IL-22 expression is associated with H pylori dependence in gastric MALT lymphoma (F. Liao, Y. C. Hsu, S.H.K., et al, unpublished data, May 15, 2013).…”
Section: Direct Effects Of H Pylori On B-cell Proliferation In Gastrimentioning
confidence: 55%
“…71 Using in vitro B-cell line models, we and other investigators have demonstrated that translocated CagA can stimulate proliferation and restrain the apoptosis of B cells through ERK activation, BAD phosphorylation, p53 accumulation, BAD phosphorylation, or upregulation of Bcl-2 and Bcl-XL expression. 22,27,72 Our current findings revealed a close link between CagA and CagA-signaling molecules, p-SHP-2, and p-ERK in the tumor cells of gastric DLBCL and that this link appears to be closely associated with HP dependence. Our results also disclosed that the cagA gene can be detected in all gastric tumor biopsies obtained from 7 selective cases of HP-dependent gastric DLBCL whose tumor were expressing CagA (supplemental Methods; supplemental Figure 3).…”
Section: Discussionmentioning
confidence: 85%
“…Deregulation of intracellular signal transducers by the injected CagA is suspected of being involved in the development of gastric pathogenesis, eventually leading to a gastric adenocarcinoma. In human B lymphocytes, overexpression of cagA through transfection induces activation of extracellular signal-regulated kinase (ERK) and their downstream apoptosis regulators, indicating that CagA has effects on the growth and survival of B lymphocytes and may play a role in the development of MALT lymphomas (21,22).…”
Section: Introductionmentioning
confidence: 99%